User Behavior towards Video Content in Mobile Devices for Designing Individualistic Prefetching Algorithm - Saaidin, Shuria; Kasiran, Zolidah; ., . (International Journal of Engineering and Technology, 2018)
Prefetching content in mobile network environment are meant to shorten users perceive waiting time. Different approaches have been taken by various literatures to provide an algorithm that is able to predict user request ahead of time. A questionnaire was design and distributed to verify approaches taken by those research using new respondents. Base on the response analyzed it is found that the most important aspect that influenced user behavior towards video content is the relevancy of the topics and WiFi is the most preferred type of connections to be used to download video content. Another behavior observed is that users who are willing to watch prefetched video also tends to download a new video. The analysis also confirms that user could be categorized to heavy and light users and they behave differently during weekdays and weekends. Findings from this survey would hopefully become guidance in designing a prefetching algorithm that suited individual needs.Â